The Aloe vera acemannan polysaccharides inhibit phthalate-induced cell viability, metastasis, and stemness in colorectal cancer cells - Pei-Chun Shih; Chung-Hsien Lin; Uvarani Chokkalingam; Ekambaranellore Prakash; Ching-Nan Kao; Chuan-Fa Chang; Wei-Ling Lin (Ecotoxicology and Environmental Safety)
Plasticizers are recognized as environmental pollutants that may be associated with a range of health concerns, including impacts on growth, development, and oncogenic risks. Previous research demonstrated that prolonged exposure to di-(2-ethylhexyl) phthalate and its metabolite mono-(2-ethylhexyl) phthalate contributes to chemotherapeutic drug resistance and stemness in colorectal cancer cells. Aloe vera, an herbaceous plant with a long-standing history in traditional medicine, has attracted considerable attention for its diverse pharmacological properties. This study aimed to investigate the therapeutic potential of polysaccharides extracted from Aloe vera, specifically focusing on their anticancer properties. We eluted polysaccharides from Aloe vera using water and ethanol, resulting in the fractions designated A50 and I50, respectively. We characterized their effects on cell viability, migration, invasion, stemness, and glycosylation of colorectal cancer cells exposed to phthalates. Comprehensive glycan analysis revealed that phthalate exposure induced alterations in glycosylation patterns in colorectal cancer cells. Treatment with A50 and I50 reversed these changes to varying degrees, indicating distinct regulatory roles of the two polysaccharide fractions in colorectal cancer cells subjected to phthalate exposure. A50 exhibited a dose-dependent reduction in cell viability induced by phthalates, whereas I50 demonstrated no such effect. Notably, I50 displayed a notable inhibitory effect on migration, invasion, and stemness induced by phthalates when compared with A50. The differing polysaccharide structures of A50 and I50 may account for their divergent effects on the malignancy of colorectal cancer cells. These findings underscore the potential of Aloe vera polysaccharides in anticancer therapy and highlight the necessity for further investigation into their clinical applications.